Cisternostomy for malignant middle cerebral artery infarction: proposed pathophysiological mechanisms and preliminary results. Issue 6 (7th June 2022) - Cardali, Salvatore Massimiliano; Caffo, Maria; Caruso, Gerardo; Scalia, Gianluca; Gorgoglione, Nicola; Conti, Alfredo; Vinci, Sergio Lucio; Barresi, Valeria; Granata, Francesca; Ricciardo, Giuseppe; Garufi, Giada; Raffa, Giovanni; et al.
Abstract : Background: The ischaemic stroke of the territory of the middle cerebral artery represents an event burdened by high mortality and severe morbidity. The proposed medical treatments do not always prove effective. Decompressive craniectomy allows the ischaemic tissue to shift through the surgical defect rather than to the unaffected regions of the brain, thus avoiding secondary damage due to increased intracranial pressure. In this study, we propose a novel treatment for these patients characterised by surgical fenestration of the cisterns of the skull base. Methods: We have treated 16 patients affected by malignant middle cerebral artery ischaemia and treated with cisternostomy between August 2018 and December 2019. The clinical history, neurological examination findings and neuroradiological studies (brain CT, CT angiography, MRI) were performed to diagnose stroke. Clinical examination was recorded on admission and preoperatively using the Glasgow Coma Scale and the National Institutes of Health Stroke Scale. Results: The study included 16 patients, 10 males and 6 females. The mean age at surgery was 60.1 years (range 19–73). Surgical procedure was performed in all patients. The patients underwent immediate postoperative CT scan and were in the early hours evaluated in sedation window. In total, we recorded two deaths (12.5%). A functional outcome between mRS 0–3, defined as favourable, was observed in 9 (64.2%) patients 9 months after discharge. A functional outcome between mRS 4–6, defined as poor, was observed in 5 (35.7%) patients 9 months after discharge. Conclusions: The obtained clinical results appear, however, substantially overlapping to decompressive craniectomy. Cisternostomy results in a favourable functional outcome after 9 months. This proposed technique permits that the patient no longer should be undergone cranioplasty thus avoiding the possible complications related to this procedure. The results are certainly interesting but higher case numbers are needed to reach definitive conclusions.